OPTIMIZING THE ROLE OF THE “PANTAI MARANG” TOURISM COMMUNITY IN THE MANAGEMENT OF PANTAI MARANG ECOTOURISM - Andi Raihana Amirah Nahda; Gusti Haqiqiansyah Gusti; Doni Darmasetiadi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to formulate a strategy for optimizing the role of the “Pantai Marang” Tourism Awareness Group (Pokdarwis) in the management of ecotourism at Pantai Marang, Kaliorang District, Indonesia. The study employed a mixed-method approach combining qualitative and quantitative methods. The qualitative approach was used to identify internal and external factors through interviews and field observations. Meanwhile, the quantitative approach was applied in the IFAS and EFAS analyses using purposive sampling involving three respondents selected based on specific criteria. Data analysis was conducted using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) method. The findings revealed that the IFAS score was 1.12 and the EFAS score was 0.50, indicating that the position of the “Pantai Marang” Pokdarwis falls within Quadrant I. This condition demonstrates that the “Pantai Marang” Pokdarwis possesses significant strengths and opportunities that support ecotourism development. Therefore, the appropriate strategy to be implemented is a growth strategy, as it offers substantial potential for supporting the development of Pantai Marang as a leading ecotourism destination.